2003
DOI: 10.1111/j.1945-5100.2003.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy of minerals in the martian meteorite Allan Hills 84001

Abstract: Abstract-We have studied carbonate and associated oxides and glasses in a demountable section of Allan Hills 84001 (ALH 84001) using optical, scanning, and transmission electron microscopy (TEM) to elucidate their origins and the shock history of the rock. Massive, fracture-zone, and fracture-filling carbonates in typical locations were characterized by TEM, X-ray microanalysis, and electron diffraction in a comprehensive study that preserved textural and spatial relationships. Orthopyroxene is highly deformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 80 publications
4
19
1
1
Order By: Relevance
“…Concomitant to the shock event, Brearley (2003) proposed that during this heating event, the meteorite was experiencing considerable thermal heterogeneity, a factor expanded upon by Treiman (2003). This possibly explains the observations of Corrigan and Harvey (2004) that high-temperature interactions between carbonate and glass were not apparent in the samples they studied, as opposed to other studies (e.g., Barber and Scott 2003). However, Brearley (2003) based his speculation on voids around magnetite whose presence was due to formation of the magnetite from siderite.…”
Section: To Heat or Not To Heat?contrasting
confidence: 53%
See 1 more Smart Citation
“…Concomitant to the shock event, Brearley (2003) proposed that during this heating event, the meteorite was experiencing considerable thermal heterogeneity, a factor expanded upon by Treiman (2003). This possibly explains the observations of Corrigan and Harvey (2004) that high-temperature interactions between carbonate and glass were not apparent in the samples they studied, as opposed to other studies (e.g., Barber and Scott 2003). However, Brearley (2003) based his speculation on voids around magnetite whose presence was due to formation of the magnetite from siderite.…”
Section: To Heat or Not To Heat?contrasting
confidence: 53%
“…It has also been suggested that the outer rim of dual rim globules was formed by thermal decomposition of siderite during a shock event to leave magnesite and magnetite (Barber and Scott 2003;Barber et al 2001;Scott et al 2002;Scott et al 1998;Treiman 2003;Golden et al 2001). Brearley (2003) speculated that fracturing of the magnetite rim matrix boundary is evidence of a volume decrease associated with magnetite formation from siderite during a shock event.…”
Section: To Heat or Not To Heat?mentioning
confidence: 99%
“…In the case of magnetites of the ALH84001 Martian meteorite, our results suggest that aggregates of anhedral, fine-grained magnetites observed by Barber and Scott (2003), typically near fracture zones, are consistent with the partial decomposition of ALH84001 carbonates, since these authors show a crystallographic orientation with the surrounding carbonate similar to that observed in the present study. This thermal decomposition probably occurred at a temperature not intense enough to fully decompose the carbonate and to coarsen the magnetites to produce larger euhedral crystals.…”
Section: Implications For Terrestrial and Extraterrestrial Magnetitessupporting
confidence: 88%
“…Indeed, detailed discussions can be found in various recent papers, most of them concluding an inorganic origin (Barber and Scott, 2003;Brearley, 2003;Treiman, 2003;Golden et al, 2004), whereas McKay et al (2003 have brought renewed support for the biogenic interpretation. Various papers related specifically to magnetism of ALH84001 have been published (Kirschvink et al, 1997;Weiss et al, 2000Weiss et al, , 2002Weiss et al, , 2004Antretter et al, 2003;Rochette et al, 2005).…”
Section: Discussionmentioning
confidence: 96%